Forgiveness and Marital Satisfaction among Wives Caused by Infidelity in Marriage - Sari, Endah Puspita; Faizah, Nur (Seurune : Jurnal Psikologi Unsyiah, 2025)
This study aims to examine the correlation between forgiveness and marital satisfaction among wives caused by infidelity in marriage less than 10 years. There were 52 female participants in this study with wife status and an experience of being cheated on by their husbands in less than 10 years of marriage. Forgiveness was measured using the Transgression Related Interpersonal Motivation 18-item (TRIM-18) scale, while marital satisfaction was measured using the Satisfaction with Married Life (SWML) scale, both adapted to the Indonesian language and culture. The results showed that 1) there was no correlation between revenge motivation and marital satisfaction (r = -0.095; p = 0.501), 2) there was a negative, significant correlation between avoidance motivation and marital satisfaction (r = -0.301; p = 0.030), and 3) there was a positive, significant correlation between benevolence motivation and marital satisfaction (r = 0.543; p = 0.000). The implication is that this study becomes the basis for the development of a forgiveness therapy module for wives as victims of infidelity.